Analytical comparison between the speed of screw and crank-rocker basedpick and place mechanisms for seedling tray seeding machine - Abdulkadir, Tukur Daiyabu; Wayayok, Aimrun; Mahadi @ Othman, Muhammad Razif; Mohd Kassim, Muhamad Saufi (University of Basrah, College of Agriculture, 2021)
In this study the operational speed of screw based pick and place mechanism was compared with that of a crank-rocker based pick and place mechanism analytically for the design of a seeding machine for system of rice intensification (SRI) seedling tray. The configurations of the two types of mechanisms were generated based on their positions relative to a seedling tray conveyor, seed container and size of seeding manifold. The screw based mechanism consists of a vertical screw to which the seeding manifold was mounted and a horizontal screw to which the vertical mechanism was mounted. The vertical screw bearing the seeding manifold reciprocates down to pick seeds from seed container and back to the initial position. The horizontal screw translates horizontally to deliver the vertical screw bearing the seeding manifold to the seedling tray on the conveyor. The crank-rocker based mechanism consists of a pair of crank-rocker carrying a seeding manifold in between them. The mechanism rotates clock wise to pick seed and counter clock wise to drop the seed on the seedling tray. The time required for a complete pick and place circle was computed for both mechanisms using basic mechanics principles. Crank-rocker mechanism with a theoretical pick and place period of 1 second was found to be better than the screw based mechanism with 78.8 second per pick and place circle.